Edukasi Literasi Keuangan Digital pada Warga Kampung Mandung, RT.02, RW.03, Desa Kopo, Kec.Kopo Kab. Serang - Rosyati, Tati; Nuryani, Anum; Fitriyana, Fina (Prodi Ekonomi Syariah Universitas Pamulang, 2023)
Lack of public knowledge and understanding of various crimes in the digital world that lead to financial benefits. Education and training are needed, especially for villagers as a provision for awareness of the threats that exist against password theft which can result in privacy and information hijacking. This education is considered important because at this time the village community, especially Kopo village, internet users rose quite high, this is evidenced by the installation of wifi in people's homes. The purpose of this Community Service activity is to increase public understanding of cyber crime through education to the public using power point-based methods and delivered directly. The results obtained after PKM is carried out are that the community better understands various types of Cyber crime and how to overcome it, this can be seen from the results of citizen questionnaires before and after participating in PKM activities.